LEGAL PROTECTION OF FOOTBALL MATCH SPECTATORS IN INDONESIA: A Case Study of the Kanjuruhan Tragedy - Wahyudin, Ahmad Fahmi; Prasetyo, Dossy Iskandar (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2025)
In a soccer match, the presence of spectators plays an important role as encouragement for the team. Spectator support, whether playing at home or away, has proven effective in boosting the players' morale. However, in some cases, rivalry between spectators may lead to anarchic actions that lead to riots. The Kanjuruhan tragedy on October 1, 2022 at Kanjuruhan Stadium, Malang, became one of the worst incidents in Indonesian football history. The riot involving police officers and spectators caused 135 casualties, all of whom came from the spectators. This research analyzes the legal protection for spectators in holding football matches. The research method used is normative research with a statutory and conceptual approach. Juridically, the spectators hold civil rights against the organizers of the match. In addition, they are also protected as consumers and guaranteed security and safety by the state through various regulations. If there is a violation of these rights, either by the organizers or police officers, legal action can be taken in accordance with applicable regulations. Based on the research findings, legal protection for spectators is regulated in the Consumer Protection Law and the Sports Law. In the Kanjuruhan case, the court decision has stated that the police officers involved were guilty and sentenced to criminal sanctions.